Sistema tutorial inteligente - Parra O, Franklin (2010)
In the teaching-learning process four key elements intervene: the student, the educational one, the information and the means that it surrounds the student. The students are related from early age with the handling of the technology, they find very motivante; for this reason always they are willing to give bigger time to activities that use the computer with the only recompense of using them. In other societies to the daily activity of the students in the class living room, he/she has been united the interaction with you scheme intelligent, in this relationship, the systems intelligent tutoriales have entered (STI) whose characteristic main they are: to promote an active answer in the student, to inform the acting, to allow an autonomous learning, to promote the efficiency and effectiveness. The STIs the same as the teacher thinks about queries like: what to teach?, when to teach? and how to teach?. Does he/she think about then if in our society it will Improve the activity of the class the use of a system intelligent tutorial for the learning of the Physics, specifically in the topic of the half speed of the particle? The answer to this query is affirmative, this it is based on the high degree of acceptance and satisfaction of the group in study toward the use of a prototype of system tutorial.